Developement and Evaluation of Egg Patties By Incorporating Chicken Gizzard - Najeeb, A. P.; Mandal, P. K.; Pal, U. K.; Rao, V. K. (Journal of Meat Science, 2012)
The current development in the fast food sector is showing a demand for processed value added egg products. Gizzard is one of the edible byproducts of poultry processing which are being marketed as variety meat along with dressed chicken. Keeping these factors in mind, an experiment was envisaged to standardize the processing methodology and formulation of egg patties incorporated with gizzard. The standardized recipe for the product contained liquid egg (92.5%), dry spices-1.5%, wet condiments ginger – garlic paste (2:1)-3%, salt-1% and maida -3%. Different levels (25, 50 & 75%) of gizzard were incorporated in the standardized recipe by replacing the liquid egg. The effect of different levels of gizzard on the physicochemical and sensory properties of egg patties were investigated. Even up to 75% incorporation of gizzard in egg patties did not show any significant difference in the cooking yield (85.89- 87.75%). Moisture level (55.05-66.15%) was significantly higher in control followed by patties containing gizzard at 25% incorporation. In contrast, protein content (11.44-22.34%) of the product was significantly higher at 75% level of gizzard incorporation. The crude fat (5.72-11.48) content did not differ significantly with different levels of incorporation of gizzard in egg patties. Similarly, the sensory scores for the product did not differ significantly for all the parameters up to 75% level of gizzard incorporation. The sensory score for appearance, flavor, juiciness, texture and overall acceptability were ranged between 5.85-6.52, 6.15-6.53, 5.95-6.34, 6.25-6.55 and 5.90-6.55, respectively. Hence, the incorporation of gizzard in egg patties will be have a favourable consumer appeal by considering its high protein value, low crude fat content with similar sensory attributes.